Human Papillomavirus Status and the Risk of Cerebrovascular Events Following Radiation Therapy for Head and Neck Cancer. Issue 9 (30th August 2017) - Addison, Daniel; Seidelmann, Sara B.; Janjua, Sumbal A.; Emami, Hamed; Staziaki, Pedro V.; Hallett, Travis R.; Szilveszter, Bálint; Lu, Michael T.; Cambria, Richard P.; Hoffmann, Udo; Chan, Annie W.; Wirth, Lori J.; et al.
Abstract : Background: Radiation therapy (RT) is a standard treatment for head and neck cancer; however, it is associated with inflammation, accelerated atherosclerosis, and cerebrovascular events (CVEs; stroke or transient ischemic attack). Human papillomavirus (HPV) is found in nearly half of head and neck cancers and is associated with inflammation and atherosclerosis. Whether HPV confers an increased risk of CVEs after RT is unknown. Methods and Results: Using an institutional database, we identified all consecutive patients treated with RT from 2002 to 2012 for head and neck cancer who were tested for HPV. The outcome of interest was the composite of ischemic stroke and transient ischemic attack, and the association between HPV and CVEs was assessed using Cox proportional hazard models, competing risk analysis, and inverse probability weighting. Overall, 326 participants who underwent RT for head and neck cancer were tested for HPV (age 59±12 years, 75% were male, 9% had diabetes mellitus, 45% had hypertension, and 61% were smokers), of which 191 (59%) were tumor HPV positive. Traditional risk factors for CVEs were similar between HPV‐positive and ‐negative patients. Over a median follow‐up of 3.4 years, there were 18 ischemic strokes and 5 transient ischemic attacks (event rate of 1.8% per year). The annual event rate was higher in the HPV‐positive patients compared with the HPV‐negative patients (2.6% versus 0.9%, P =0.002). In a multivariable model, HPV‐positive status was associated with a >4 times increased risk of CVEs (hazard ratio: 4.4; 95% confidence interval, 1.5–13.2; P =0.008). Conclusions: In this study, HPV‐positive status is associated with an increased risk of stroke or transient ischemic attack following RT for head and neck cancer.